2018
DOI: 10.1002/ijc.31587
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in risk of prostate cancer: ASwedish population‐based cohort study of competing risks and Type 2 diabetes mellitus

Abstract: Most previous studies of prostate cancer have not taken into account that men in the studied populations are also at risk of competing event, and that these men may have different susceptibility to prostate cancer risk. The aim of our study was to investigate heterogeneity in risk of prostate cancer, using a recently developed latent class regression method for competing risks. We further aimed to elucidate the association between Type 2 diabetes mellitus (T2DM) and prostate cancer risk, and to compare the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…[7][8][9] For example, the presence and absence of an intrasellar pituitary gland can help distinguish suprasellar and intrasellar tumors, i. e. pituitary tumors. 10,11 However, suprasellar tumors often invade into the sellar and compress the pituitary to move backward, and the imaging appearance is crescent. Enhanced MRI usually shows the characteristic signs of sellar region tumors, such as "meningioma tail sign", which is the gold standard for the diagnosis of meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] For example, the presence and absence of an intrasellar pituitary gland can help distinguish suprasellar and intrasellar tumors, i. e. pituitary tumors. 10,11 However, suprasellar tumors often invade into the sellar and compress the pituitary to move backward, and the imaging appearance is crescent. Enhanced MRI usually shows the characteristic signs of sellar region tumors, such as "meningioma tail sign", which is the gold standard for the diagnosis of meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of T2D on PCa is complex [ 7 ], and the relationship is influenced by numerous factors that are difficult to assess individually [ 12 ]. While a large number of studies have reported a lower PCa risk in patients with T2D [ 13 ], they are characterized by more advanced PCa than patients with normal glucose metabolism [ 8 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation of these individuals can therefore help to uncover indicators for either preventative or therapeutic measures. 21 Therefore, replica analysis and further AI techniques may be useful for prediction models in the real world settings.…”
Section: Artificial Intelligence – Is It Worth the Hype?mentioning
confidence: 99%